2017
DOI: 10.1038/s41598-017-16351-z
|View full text |Cite
|
Sign up to set email alerts
|

High corrosion resistance and weak corrosion anisotropy of an as-rolled Mg-3Al-1Zn (in wt.%) alloy with strong crystallographic texture

Abstract: Combining with electrochemical corrosion measurements, immersion and hydrogen evolution testing performed in 0.9 wt.% NaCl solution at 37 °C, the corrosion resistance of an as-rolled Mg-3%Al-1%Zn alloy before and after a 3% compressive strain along the rolling direction was investigated. Results revealed that the corrosion behavior of differently oriented surfaces of the as-rolled samples with a strong basal texture was obviously different. Among them, the corrosion rate of sample surface with the orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…It can be inferred that the corrosion resistance of magnesium alloy may be changed with the evolution of crystal texture caused by applied force. The effect of grain orientation or plastic deformation on the corrosion resistance of magnesium alloys in NaCl solution has been reported by some researchers [11][12][13][14][15]. However, the texture effect of applied force on corrosion resistance of magnesium alloys in physiological environment has not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be inferred that the corrosion resistance of magnesium alloy may be changed with the evolution of crystal texture caused by applied force. The effect of grain orientation or plastic deformation on the corrosion resistance of magnesium alloys in NaCl solution has been reported by some researchers [11][12][13][14][15]. However, the texture effect of applied force on corrosion resistance of magnesium alloys in physiological environment has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Other is the corrosion effect induced by applied force related to plastic deformation. Plastic deformation process affected the microstructure (such as grain size and dislocation density) and thus changed the corrosion resistance of magnesium alloy [14,15]. The previous work of the author showed that the crystal texture of magnesium alloy was changed when the rolled or extruded magnesium alloy was subjected to applied forces along different material orientations [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, the experimental EIS data were fitted by using the zSimWin 3.21 software. The simulated equivalent circuit diagram is shown in Figure 7 c. Among them, R s is the solution resistance, R t is the charge transfer resistance at the electrolyte solution interface, R f is the corrosion product resistance, and CPE d and CPE f , respectively, represent the corrosion product film capacity and galvanic double-layer capacity at the interface between the Mg matrix and the electrolyte solution, and are generally used to characterize the high-frequency capacitor loop [ 23 ]. According to the equivalent circuit, the Nyquist diagrams of the WE43 samples before and after rolling were obtained by using ZsimpWin 3.50 software to obtain the fitted values.…”
Section: Resultsmentioning
confidence: 99%
“…How these microstructural features at the grain scale impact the electrochemical performance largely remains underexplored. For example, the corrosion resistance of a rolled Mg alloy is shown to be dependent more on the density of twin boundaries than on the surface textures . There is substantial room for fundamental research and commercial development by borrowing the metallurgists’ wisdom to interrogate metals’ electrochemical performance in practical batteries.…”
Section: Scalable Approaches For Fabricating Textured Electrodesmentioning
confidence: 99%